Engagement of the Mannose Receptor by Tumoral Mucins Activates an Immune Suppressive Phenotype in Human Tumor-Associated Macrophages - P. Allavena; M. Chieppa; G. Bianchi; G. Solinas; M. Fabbri; G. Laskarin; A. Mantovani (Clinical and Developmental Immunology)
Tumor-Associated Macrophages (TAMs) are abundantly present in the stroma of solid tumors and modulate several important biological processes, such as neoangiogenesis, cancer cell proliferation and invasion, and suppression of adaptive immune responses. Myeloid C-type lectin receptors (CLRs) constitute a large family of transmembrane carbohydrate-binding receptors that recognize pathogens as well as endogenous glycoproteins. Several lines of evidence demonstrate that some CLRs can inhibit the immune response. In this study we investigated TAM-associated molecules potentially involved in their immune suppressive activity. We found that TAMs isolated from human ovarian carcinoma samples predominantly express the CLRs Dectin-1, MDL-1, MGL, DCIR, and most abundantly the Mannose Receptor (MR). Components of carcinomatous ascites and purified tumoral mucins (CA125 and TAG-72) bound the MR and induced its internalization. MR engagement by tumoral mucins and by an agonist anti-MR antibody modulated cytokine production by TAM toward an immune-suppressive profile: increase of IL-10, absence of IL-12, and decrease of the Th1-attracting chemokine CCL3. This study highlights that tumoral mucin-mediated ligation of the MR on infiltrating TAM may contribute to their immune suppressive phenotype.